Saquinavir Ameliorates Liver Warm Ischemia-Reperfusion-Induced Lung Injury via HMGB-1- and P38/JNK-Mediated TLR-4-Dependent Signaling Pathways - Zhuang Yu; Yao Tong; Renlingzi Zhang; Xibing Ding; Quan Li (Hindawi Limited, 2017)
Liver ischemia and reperfusion (I/R) induce local and distant tissue injuries, contributing to morbidity and mortality in a wider range of pathologies. This is especially seen under uncontrolled aseptic inflammatory conditions, leading to injury of remote organs, such as lung injury, and even failure. Saquinavir (SQV) is a kind of HIV protease inhibitor that possesses an anti-inflammatory property. In this study, we investigated whether SQV suppresses Toll-like receptor 4- (TLR4-) dependent signaling pathways of high-mobility group box 1 (HMGB1) and P38/JNK, conferring protection against murine liver I/R-induced lung injury. To investigate our hypothesis, C57BL/6 mice and TLR4 knockout mice (TLR4−/−) were used to perform the study. SQV administration markedly attenuated remote lung tissue injury after 1-hour ischemia and 6-hour reperfusion of the liver. To our expectation, SQV attenuated I/R-induced lung edema, hyperpermeability, and pathological injury. The beneficial effects of SQV were associated with decreased levels of circulating and lung tissue inflammatory cytokines, such as IL-6, IL-1β, TNF-α, and iNOS. The protective effect of SQV was also associated with decreased lung tissue expression of HMGB1, TLR-4, and p-P38/JNK, but not p-ERK in wild-type liver I/R mice. Overall, this study demonstrated a new role of SQV, facilitating negative regulation of HMGB1- and P38/JNK-mediated TLR-4-dependent signaling pathways, conferring protection against liver I/R-induced lung injury.